Penerapan Metode Quality Function Deployment (QFD) Pada Peningkatan Mutu Produk Milk Chocolate Di Wisata Edukasi Doesoen Kakao, Glenmore, Banyuwangi - Wardhana, Danu Indra; Ronita, Alda Wata Alim; Setiawan, Andika Putra (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Doesoen Kakao experienced a decline caused by a sales strategy that was not optimal, such as the lack of digital and direct product promotion and the lack of following changing consumer trends as well as the emergence of competitors with more attractive products in terms of packaging, price, and taste. Therefore, efforts are needed to improve product quality, one of which is by applying the Quality Function Deployment (QFD) method. This study aims to analyze the level of satisfaction with Milk Chocolate Glen products when compared to competitors and analyze recommendations for improvement of the quality attributes of Milk Chocolate Glen products after the application of the QFD method. The method that can be used in this study is QFD.The selected respondents amounted to 50 people, namely consumers who had consumed Glen Milk Chocolate between the ages of 17-52 years. Based on the results of the research on packaging attributes have the highest improvement ratio, which is 1.43, this shows that companies need to add clarity of information such as expiration dates and the inclusion of halal labels, as well as make packaging designs more attractive. The second attribute is the price with an improvement ratio value of 1.28, the company can offer various price variants according to market segments, such as economical packaging for consumers with lower purchasing power. The third attribute is taste with an improvement ratio value of 1.2, the taste attribute must be improved because it is the main factor that affects consumer satisfaction and loyalty. Doesoen Kakao experienced a decline caused by a sales strategy that was not optimal, such as the lack of digital and direct product promotion and the lack of following changing consumer trends as well as the emergence of competitors with more attractive products in terms of packaging, price, and taste. Therefore, efforts are needed to improve product quality, one of which is by applying the Quality Function Deployment (QFD) method. This study aims to analyze the level of satisfaction with Milk Chocolate Glen products when compared to competitors and analyze recommendations for improvement of the quality attributes of Milk Chocolate Glen products after the application of the QFD method. The method that can be used in this study is QFD.The selected respondents amounted to 50 people, namely consumers who had consumed Glen Milk Chocolate between the ages of 17-52 years. Based on the results of the research on packaging attributes have the highest improvement ratio, which is 1.43, this shows that companies need to add clarity of information such as expiration dates and the inclusion of halal labels, as well as make packaging designs more attractive. The second attribute is the price with an improvement ratio value of 1.28, the company can offer various price variants according to market segments, such as economical packaging for consumers with lower purchasing power. The third attribute is taste with an improvement ratio value of 1.2, the taste attribute must be improved because it is the main factor that affects consumer satisfaction and loyalty.